2020
DOI: 10.1002/dvdy.237
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in the developing vertebrate limb: A locally regulated mechanism contributing to musculoskeletal tissue morphogenesis and differentiation

Abstract: Our aim is to critically review current knowledge of the function and regulation of cell death in the developing limb. We provide a detailed, but short, overview of the areas of cell death observed in the developing limb, establishing their function in morphogenesis and structural development of limb tissues. We will examine the functions of this process in the formation and growth of the limb primordia, formation of cartilaginous skeleton, formation of synovial joints, and establishment of muscle bellies, ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 128 publications
1
20
0
Order By: Relevance
“…Studies in a variety of models of embryonic tissue degeneration indicate that rather than being inherently programmed, cell death is locally regulated by extrinsic molecular interactions. The plasticity of the interdigital tissue in stages immediately prior to the onset of death provides solid support for the importance of extrinsic signals in the establishment of the degenerative process (see review by Montero et al, 2020). In addition, as will be discussed below, accumulating evidence has revealed that, far from being a unique way of embryonic cell death, apoptosis is only one among several redundant dying mechanisms accounting for the elimination of tissues in the course of embryonic development (Childs et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Studies in a variety of models of embryonic tissue degeneration indicate that rather than being inherently programmed, cell death is locally regulated by extrinsic molecular interactions. The plasticity of the interdigital tissue in stages immediately prior to the onset of death provides solid support for the importance of extrinsic signals in the establishment of the degenerative process (see review by Montero et al, 2020). In addition, as will be discussed below, accumulating evidence has revealed that, far from being a unique way of embryonic cell death, apoptosis is only one among several redundant dying mechanisms accounting for the elimination of tissues in the course of embryonic development (Childs et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…The best known cell death areas are the so called Anterior Necrotic Zone (ANZ), Posterior Necrotic Zone (PNZ) and the Opaque Patch (OP) 19,20 . Additionally, the apical ectodermal ridge (AER) is an ectodermal thickening in the distal edge of the limb bud that maintains a fine-tuned equilibrium between cell death and proliferation 20 .…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…The best known cell death areas are the so called Anterior Necrotic Zone (ANZ), Posterior Necrotic Zone (PNZ) and the Opaque Patch (OP) 19,20 . Additionally, the apical ectodermal ridge (AER) is an ectodermal thickening in the distal edge of the limb bud that maintains a fine-tuned equilibrium between cell death and proliferation 20 . There are three main signaling regions that direct morphogenesis controlling early limb bud development: the AER; the underlying mesoderm, also known as the progress zone (PZ); and the zone of polarizing activity (ZPA) in the posterior mesenchyme of the early limb.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these degradative routes, oxidative stress might exert an important role in the establishment of areas of interdigital cell death [9][10][11]. Although we do not know yet how these degenerative routes are coordinated or whether they are regulated by other signals, it has been shown that interdigit degradation is preceded by intense DNA damage and by activation of a DNA repair response [12,13]. A similar process also occurs in cancer and is associated with epigenetic alterations, such as DNA methylation or post-translational histone modifications [14].…”
Section: Introductionmentioning
confidence: 99%